Private Higher Education: Advancing Discovery - Levy, Daniel (International Higher Education, 2025)
<h3 id="the-vast-global-expansion-of-private-higher-education-to-over-80-million-students-a-third-of-total-enrollment-and-near-ubiquity-by-country-has-brought-formidable-additional-differentiation-and-complexity-within-the-worlds-higher-education-undertakings-and-stakeholder-configurations-leading-research-has-captured-vital-dimensions-of-this-differentiation-including-through-private-public-and-private-private-comparisons-in-addition-to-the-dissemination-of-this-discovered-knowledge-the-further-expansion-of-knowledge-rests-largely-upon-building-directly-upon-the-considerable-advances" data-pm-slice="1 1 []">The vast global expansion of private higher education to over 80 million students, a third of total enrollment, and near ubiquity by country, has brought formidable additional differentiation and complexity within the world’s higher education undertakings and stakeholder configurations. Leading research has captured vital dimensions of this differentiation, including through private-public and private-private comparisons. In addition to the dissemination of this discovered knowledge, the further expansion of knowledge rests largely upon building directly upon the considerable advances.